Aneurysm healing after endovascular treatment in the Helsinki sidewall aneurysm model: a systematic review. (11th October 2022) - Rinaldo, Lorenzo; Arturo Larco, Jorge L; Kadirvel, Ramanathan; Kallmes, David F
Abstract : Aims: Intracranial aneurysms are treated with a variety of endovascular devices including coils, stents, and flow diverters. The mechanisms by which these devices result in aneurysm occlusion and subsequent healing have been the subject of significant research using various animal models. The murine Helsinki aneurysm model is a sidewall aneurysm created by the end-to-side anastomosis of a donor aortic graft onto the abdominal aorta of a recipient animal. The aim of this systematic review is to assess the efficacy of different endovascular devices for the treatment of the Helsinki model aneurysm. Methods: We performed a systematic review of Pubmed in accordance with PRISMA guidelines, yielding eight studies detailing the results of endovascular treatment of this preclinical aneurysm model. Studies were included if they provided rates of complete aneurysm occlusion after treatment. Results: In these studies, aneurysms were treated with coiling (n=81, 7 studies), stenting (n=67, 3 studies), stent-coiling (n=13, 1 study), and flow diversion (n=49, 2 studies). The results of each individual study are discussed with the goal of providing a measure of the relative efficacy of different endovascular devices for the treatment of this particular model aneurysm. We also pay special attention to insights into the mechanisms underlying aneurysm healing after different forms of endovascular therapy. Conclusion: The data presented here may be useful to investigators attempting to demonstrate superiority of novel endovascular devices relative to previous device iterations using this preclinical model.